Kemungkinan Pemanfaatan Beberapa Jenis Rotan Non Komersial Ditinjau Dari Sifat-Sifat Fisik Mekanik - Heriad Daud S alusu; Eva Nurmarini; Ita Merni Patulak (P2M Politeknik Pertanian Negeri Samarinda, 2020)
This research was conducted to determine the basic properties of rattan which are related to the possibility of its use, which are physical-mechanical properties consisting of moisture content, density, parallel tensile strength and modulus of elasticity. There were 12 species of non-commercial rattan studied, 11 species included in the small diameter rattan category (<18 mm diameter) and 1 species belonging to the large diameter rattan category (> 18 mm diameter), namely Daemonorops korthlasii Blume. Based on the results of the tests carried out, there are three species of non-commercial rattan that have similar or similar basic properties to commercial rattan, namely Calamus conirostris Becc., Korthalsia ferox Becc., and Calamus muricatus Becc.